Fashion communication in times of pandemic: how fashion brands built a discourse in digital media (ModaPalavra e-periódico, 2022)
The year 2020 was marked by the scenario of the Covid-19 pandemic, a virus that caused many deaths among the world population and transformed the way of interaction and social relationships in the world. The fashion industry is responsible for a significant portion of world consumption, being consequently affected by this context. The study aimed to analyze the content presented by companies Riachuelo (fast fashion production model) and Flávia Aranha (slow fashion production model) on their website and social network Instagram, from March to May 2020, to understand which strategies were used and how companies positioned themselves in digital media during this clipping of the pandemic. The results indicated some similar perspectives and some differences in the focus of the companies' content on this topic. Riachuelo and Flávia Aranha, in addition to creating content in their online media, also carried out social and advertising actions and created products/services that suited this period.
Keywords: Digital communication in 2020; Fast fashion; Slow fashion